Exosome-Transmitted miR-25 Induced by H. pylori Promotes Vascular Endothelial Cell Injury by Targeting KLF2 - Li, Na; Liu, Shi-feng; Dong, Kai; Zhang, Gui-chun; Huang, Jing; Wang, Zhi-heng; Wang, Tong-jian (Frontiers in Cellular and Infection Microbiology, 2019)
Background: Increasing evidence has shown that Helicobacter pylori (H. pylori) is involved in coronary heart disease (CHD), but the underlying mechanism remains unclear. Methods: The expression of miR-25 and mRNAs was measured using qRT-PCR. Protein levels were detected using western blotting. Exosome was estimated using electron microscope. The target gene of miR-25 was identified using luciferase report system. Results: H. pylori infection increases the expression of miR-25 in gastric epithelial cells and is associated with increased levels of exosome-transmitted miR-25 in human peripheral blood. Mechanistic investigation shows Kruppel-like factor 2 (KLF2) as a direct target of exosome-transmitted miR-25 in vascular endothelial cells, and miR-25/KLF2 axis regulates the NF-κB signaling pathway, resulting in increased expression of IL6, MCP-1, VACM-1 and ICAM-1. Conclusion: Our findings suggest that miR-25/KLF2 axis may be a potential therapeutic target for H. pylori-associated CHD and high level of exosome-transmitted miR-25 in peripheral blood may be a potential risk of CHD.